Assessment of Possible Drug Interactions in Patients with Psoriasis and Associated Comorbid Medical Conditions: An Observational Study - Sherin, Reena; Udaykumar, Padmaja (Reviews on Recent Clinical Trials, 2016)
Background: Associated co-morbidities with psoriasis are treated with concomitant medications apart from the antipsoriatic therapy and the resulting Drug-Drug Interactions (DDI) may affect therapeutic outcome. Objective: To assess the DDI in psoriatic patients with co-morbidities. Method: In this prospective observational analysis, 150 prescriptions of psoriatic patients, receiving two or more drugs were analysed using drug interaction checker software. DDI was classified into minor, moderate, major and pharmacokinetic & pharmacodynamic. Result: Of 150 patients, 77.3% (n=116) had cardiovascular comorbities; diabetes mellitus (49.3%), psoriatic arthritis (20.7%), hyperlipidemia (46%), infections (28.7%), neurologic conditions (24.7%) and dermatologic conditions (37.3%) were other reported comorbidities. Of these, 138 (92%) patients had 612 DDI (4.49 interactions/patient). More number of interactions were seen in 45-60 yrs (n=311, 50.8%). Moderate DDI (79.9%) were higher; 306 (50%) were pharmacokinetic interactions. Frequent interactions were due to non-steroidal anti-inflammatory drugs (n=229, 37.4%) and antibiotics (n=176, 28.8%). Monitoring of the signs & symptoms was the advised intervention in 67.2% of patients. Mean DDI per patient was more in those who received >10 drugs (9.67). There was an increased number of DDI with an increase in the number of medications which was statistically significant (p<0.01), with greater number of (n=458, 74.8%) interactions seen in those who received 5-10 drugs. Conclusion: There was an increased number of DDI in those who received more number of drugs. Careful monitoring with appropriate timely laboratory investigations, and a rational drug prescription for the comorbid conditions can prevent the occurrence of harmful DDIs.
Keywords: rational drug prescription